Analisis Risiko dan Tingkat Pengembalian Terhadap Investasi Bitcoin di Indonesia - Septiana Nur Anggraeni; Vega Anismadiyah (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the risk level and rate of return of Bitcoin investment in Indonesia during the period 2020–2024. Bitcoin was selected as the research object due to its high volatility and its position as the cryptocurrency with the largest market capitalization. This research employs a quantitative descriptive approach using secondary data in the form of monthly closing prices obtained from CoinMarketCap and Investing.com. Data analysis was conducted by calculating monthly returns, standard deviation as a measure of risk, and coefficient of variation to assess investment efficiency. The results show that Bitcoin has a risk level of 19.79%, indicating high price volatility. However, Bitcoin generated significant returns in several periods, particularly in 2020, 2021, and 2024. These findings confirm that Bitcoin is characterized as a high-risk, high-return investment. Thus, Bitcoin investment is more suitable for aggressive investors with high risk tolerance rather than conservative investors.